(untitled) (International Journal of Environmental Sciences, 2024)
The widespread use of synthetic insecticides has raised concerns regarding environmental persistence, resistance development, and non-target toxicity, necessitating the exploration of sustainable alternatives. Piper nigrum derived phytochemicals have attracted considerable attention due to their broad spectrum bioactivity and ecological compatibility. The present study investigates the phytochemical composition of P. nigrum and their molecular interactions with key insect targets. Major constituents, including Piperin and related alkaloids, were identified and evaluated for their binding affinity and interaction stability with proteins involved in insect metabolic pathways. Molecular interaction analysis revealed strong and specific ligand–target associations, suggesting potential mechanisms underlying insecticidal activity. These findings provide significant insights into the insecticidal potential of P. nigrum phytochemicals and support their development as eco-friendly alternatives to synthetic insecticides.